Are We Aware of Racism? How Ethno-racial Categories, Skin color and Miscegenation Shape the Recognition of Racism in Colombia - Vasquez-Padilla, Dario Hernan (Sociedad y Economía, 2019)
This article examines the effect of ethnic-racial categories, skin color, and miscegenation on individuals’ per- ception on racism in Colombia. Utilizing ordered logistic regression models on a national sample from the 2010 and 2011 America’s Barometer, it is found that ethnic-racial self-identification categories and the recognition of racism are not associated, while darker-skinned individuals have a higher probability of recognizing this phe- nomenon. Findings also reveal that desiring to have a lighter skin color, understood as part of the whitening logic of miscegenation, has a strong negative association. This article contributes to the studies on racism in Latin America and calls for rethinking the use of ethnic-racial categories and the role of skin color in the analy- sis of racialized systems.